Acute Kidney Injury, Recurrent Seizures, and Thrombocytopenia in a Young Patient with Lupus Nephritis: A Diagnostic Dilemma - Hector Alvarado Verduzco; Anjali Acharya (Case Reports in Nephrology)
Introduction. Posterior reversible encephalopathy syndrome (PRES) is a constellation of clinical and radiologic findings. Fluctuations in blood pressure, seizures, and reversible brain MRI findings mainly in posterior cerebral white matter are the main manifestations. PRES has been associated with multiple conditions such as autoimmune disorders, pregnancy, organ transplant, and thrombotic microangiopathy (TMA). Case Presentation. A 22-year-old woman with history of Systemic Lupus Erythematous complicated with chronic kidney disease secondary to lupus nephritis class IV presented with recurrent seizures and uncontrolled hypertension. She was found to have acute kidney injury and thrombocytopenia. Repeat kidney biopsy showed diffuse endocapillary and extracapillary proliferative and membranous lupus nephritis (ISN-RPS class IV-G+V) and endothelial swelling secondary to severe hypertension but no evidence of TMA. Brain MRI showed reversible left frontal and parietal lesions that resolved after controlling the blood pressure, making PRES the diagnosis. Conclusion. PRES is an important entity that must be recognized and treated early due to the potential reversibility in the early stages. Physicians must have high suspicion for these unusual presentations. We present a case where performing kidney biopsy clinched the diagnosis in our patient with multiple confounding factors.